Uterine Carcinosarcoma: A Case Report and Literature Review - Ali Kord; Behnam Rabiee; Ismail Elbaz Younes; Karen L. Xie (Case Reports in Obstetrics and Gynecology)
Uterine carcinosarcomas are rare and extremely aggressive undifferentiated carcinomas which include both carcinomatous and sarcomatous elements. A 52-year-old female presented with heavy irregular menstrual bleeding for several years and new right elbow pain and swelling. Ultrasound and computed tomography showed a large uterine mass with regional and distant metastatic lymphadenopathy and suspicious findings of osseous metastasis to the right elbow. A biopsy confirmed uterine carcinosarcoma, and the patient underwent chemotherapy and then surgical resection of the uterine mass with palliative radiotherapy of the right elbow. The postoperative imaging showed new metastasis, and the patient was scheduled to start on immunotherapy. Considering the highly invasive nature of uterine carcinosarcomas, timely detection of this cancer using characteristic imaging and pathology findings is of extreme importance to improve the patient’s survival.